2003
DOI: 10.1115/1.1623761
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Analysis of the Ball Screw Mechanism Considering Variable Contact Angles and Elastic Deformations

Abstract: The theoretical analyses developed by Lin et al. 6 for the kinematics of the ball screw mechanism have been partly adapted for the present study. In order to better understand the sliding behavior arising at two contact areas, the analyses of a ball bearing, while accounting for elastic deformation, are modified through coordinate transformations prior to their applications to the analyses for the ball screw mechanism. The influence of differing the parameters such as friction coefficient, normal force acting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
101
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 11 publications
1
101
0
Order By: Relevance
“…The most important studies have been done by Levit [1] [2] and in general these approaches are based on the settled theories developed for ball bearings [3]. More recently a revision of Levit's work has been proposed and more generally to the classical approach to the study of ball screw kinematic [4][5][6][7] introducing pseudosliding in nut-screw contact. Indeed the analysis of the movement of the balls during the working cycle has shown microslipping in the contact areas.…”
Section: Introductionmentioning
confidence: 99%
“…The most important studies have been done by Levit [1] [2] and in general these approaches are based on the settled theories developed for ball bearings [3]. More recently a revision of Levit's work has been proposed and more generally to the classical approach to the study of ball screw kinematic [4][5][6][7] introducing pseudosliding in nut-screw contact. Indeed the analysis of the movement of the balls during the working cycle has shown microslipping in the contact areas.…”
Section: Introductionmentioning
confidence: 99%
“…Now the mainstream approach for this problem of kinematics and dynamics analysis for the ball screw is using the numerical method. Due to a ball bearing with a ball screw on the principle of similarity and has a longer history in application and research, so the analysis of the ball bearing has certain inheritance and reference for the research of ball screw Wei and Lin (2003). Jones (1960) introduced the raceway control theory in the process of studying dynamics for the ball bearing.…”
Section: Introductionmentioning
confidence: 99%
“…We assumed that all balls in the ball screw are equally loaded and run at the same speed. According to the relationship of slipping and mechanical efficiency for ball screw, in order to verify the accuracy of the slipping model is set up, FrenetSerret Coordinates used by Wei and Lin (2003) is decided to adopt to analyze slipping of the ball screw. Through in-depth studying the slipping model for ball screw at high speeds, it is not only give a method to reduce slipping and improving the mechanical efficiency of ball screw and rolling bearing operating at high speeds but also provide theory basis for analyzing of friction and wear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to affect the wear and precision retaining ability of the BSM. Wei [1][2][3] introduced the theory of differential geometry of curve to analyze the motion rules of a ball considering the effect of the elastic deformation of contact angle and found that the self-spin and rotational angular velocities of the ball have an approximately linear relationship with the rotational velocity of the screw. Lin et al [4][5] confirmed the existence of both the rolling and sliding motions relative to each other between the ball and raceway during the operation of BSM and proposed a calculation model to estimate the transmission efficiency.…”
Section: Introductionmentioning
confidence: 99%